Exploring the Structure–Activity Relationship on Platinum Nanoparticles - Braunwarth, Laura; Jung, Christoph; Jacob, Timo (Topics in catalysis, 2020)
The design of active and stable Pt-based nanoscale electrocatalysts for the oxygen reduction reaction (ORR) plays the central role in ameliorating the efficiency of proton exchange membrane fuel-cells towards future energy applications. On that front, theoretical studies have contributed significantly to this research area by gaining deeper insights and understanding of the ongoing processes. In this work, we present an approach capable of characterizing differently-shaped platinum nanoparticles undergoing thermally- and adsorbate-induced restructuring of the surface. Further, by performing ReaxFF-Grand Canonical Molecular Dynamics simulations we explored the water formation on these roughened (“realistic”) nanoparticles in a H 2 /O 2 environment. Taking into consideration the coverage of oxygen-containing intermediates and occurring surface roughening the nanoparticles’ activities were explored. Hereby, we succeeded in locally resolving the water formation on the nanoparticles’ surfaces, allowing an allocation of the active sites for H 2 O production. We observed that exposed, low-coordinated sites as well as pit-shaped sites originating from roughening of vertices and edges are most active towards H 2 O formation.